Ciência atraente e recreativa: revistas populares de divulgação científica, Argentina e Brasil (1928-1960) - Catarina Capella Silva (2013)
In this thesis, we analyze under the perspective of comparative study, four scientific publications edited in Brazil and Argentina from 1928 to 1960, in order to understand how the process of dissemination of scientific culture in Brazilian and Argentinean societies was built. As a source of research we used Brazilian publications of Ciência Popular and Ciência Ilustrada and the Argentine titles among which presents the homonymous edition of the Brazilian Ciência Popular and the issues of the Hobby magazine. We consider as a starting year 1928, when the first edition of the first issue of Argentinean Ciência Popular Magazine came out and we finish in 1960, when the Brazilian Ciência Popular Magazine closes its activities. This is a period of political, economical and social issues that affected both countries. Argentine society was marked by the processes of urbanization, literacy and economic modernization. The ideology of scientific knowledge and technique would eventually guide new values in the literate elite of the country and on the path of progress the scientific journals would encompass the Argentine popular culture. During this period, in Brazil, the ideology of progress and modernity also caused changes that would eventually spread throughout society. However, only after the Second World War, there was a significant increase of scientific dissemination initiatives in Brazil. We observed that one of the main arguments common to all publications was the concern to raise the cultural level of the population. More than the transmission of facts and knowledge, the proposals sought to establish a scientific culture in society. In Argentina the increase in cultural activities among the "lower classes", in the early twentieth century, was linked to the increased literacy of Buenos Aires society. With a greater number of literate people access to knowledge has become more comprehensive. In this movement of a new cultural conformation in society, Argentine scientific magazines dissemination gained an important significance for the dissemination of scientific knowledge in society. During the same period, we havent found a similar movement in Brazil, which can be attributed to poor performance of the educational policies of national character. Such educational policies only gained momentum from the 1930s, when the state becomes its central articulator. This did not occur in Argentina about which we can observe the policies of educational broadcasting initiative taken by Sarmiento in the nineteenth century. On the other hand, the magazines were addressed to young students and had as its purpose to disclose scientific and technical knowledge that could contribute to the training of an industrial workforce. All journals considered essential to familiarize its readers with information in order to awaken vocations for industries. During the research we identified some aspects that shaped the Brazilian and Argentinean magazines as scientific divulgation as well as the different arguments and proposals presented in publications for the difusion of science. The examination of issues also helped identify how the magazines conveyed a certain image of science. Furthermore, we seek to understand the interaction of magazines with readers through the letters to perceive the contradictions and social transformations, and especially the process of ownership occurred.